Digital Content Marketing on Buying Decision: Literature Review - Afifa, Nurul Hildha; Sudarmiatin (Business and Investment Review, 2023)
Digital content marketing on buying decisions, the aim is to review existing literature on digital content marketing and buying decisions, namely that through content marketing you can increase interest in visiting a product so that it becomes a decision to purchase goods or services, and understand the stages of buying. decision. By using the literature method, by searching for research data or information through reading scientific journals, reference books and publication materials available in libraries and the internet. and the results of this research are studied in this article so it can be concluded to build a hypothesis for further research, namely: 1) digital content marketing has an influence on improving purchasing decisions. 2) Through content marketing, you can increase interest in visiting a product so that it becomes a decision to purchase goods or services. There are five stages of buying decision including: problem or need recognition, information search, alternative evaluation, purchase, and post purchase behavior